2012
DOI: 10.1111/j.1365-2567.2012.03627.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic mast cell activation disease: the role of molecular genetic alterations in pathogenesis, heritability and diagnostics

Abstract: SummaryDespite increasing understanding of its pathophysiology, the aetiology of systemic mast cell activation disease (MCAD) remains largely unknown. Research has shown that somatic mutations in kinases are necessary for the establishment of a clonal mast cell population, in particular mutations in the tyrosine kinase Kit and in enzymes and receptors with crucial involvement in the regulation of mast cell activity. However, other, as yet undetermined, abnormalities are necessary for the manifestation of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 90 publications
(136 reference statements)
4
44
0
2
Order By: Relevance
“…Although no formal survival studies have been reported, MCAS appears to course similarly to indolent SM, that is, life of normal span, if morbid until the disease is diagnosed and effectively controlled. Most MCAD-associated mutations appear somatic, 12 but familial MCAD appears common and may be an epigenetic phenomenon. 13,14 Approximately 75% of index patients with MCAD have at least 1 afflicted first-degree relative, 13 suggesting substantial inheritability.…”
Section: Lb Afrin and A Khorutsmentioning
confidence: 98%
See 3 more Smart Citations
“…Although no formal survival studies have been reported, MCAS appears to course similarly to indolent SM, that is, life of normal span, if morbid until the disease is diagnosed and effectively controlled. Most MCAD-associated mutations appear somatic, 12 but familial MCAD appears common and may be an epigenetic phenomenon. 13,14 Approximately 75% of index patients with MCAD have at least 1 afflicted first-degree relative, 13 suggesting substantial inheritability.…”
Section: Lb Afrin and A Khorutsmentioning
confidence: 98%
“…11 Only preliminary epidemiologic data on MCAS have been reported. In Germany, the prevalence of MCAD has been estimated at 5% to 10% of the general population, [11][12][13] which may be unsurprising because MCAS may underlie many common conditions in subsets of patients, such as those with fibromyalgia and irritable bowel syndrome (IBS). 2 CM cases outnumber SM by 10 to 1.…”
Section: Mast Cell Activation Disease Epidemiology Natural History mentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired mast cell apoptosis and interleukin 6 have also been postulated to be involved, as evidenced by BCL-2 up-regulation and IL-6 elevation in tissue. Some activating point mutation of c-kit in codon 816 (usually KITD816V), encoding the tyrosine kinasereceptor for stem cell factor, are found to be associated with systemic form [85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Since Omalizumab reduces the expression of FcεRI on circulating basophils and mast cells, it seems to lower the activity potentials of basophils and mast cells, thereby reducing the potential reactivity of these cells [81,88].…”
Section: Omalizumab Effects On Hyperimmunoglobulin-e Syndrome Eosinomentioning
confidence: 99%